2020
DOI: 10.1109/access.2020.3007656
|View full text |Cite
|
Sign up to set email alerts
|

A Novelty Approach to Retina Diagnosing Using Biometric Techniques With SVM and Clustering Algorithms

Abstract: A method to extract the retina characteristic points for the purpose of medical diagnosis of the human eye is presented in this research. The proposed method helps to make the primary decision about the illness faster and can be used on mobile devices. The algorithm is mostly based on the characteristic points (the so-called minutiae). These structures are commonly used in the biometric applications for fingerprintbased people recognition. In the case of the conducted research, this trait was used to different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…This algorithm was also selected due to its high efficiency. Moreover, the authors also proven its usefulness in their previous research [25]. During experiments, the authors observed that linear classification is much more accurate than nonlinear.…”
Section: Resultsmentioning
confidence: 73%
“…This algorithm was also selected due to its high efficiency. Moreover, the authors also proven its usefulness in their previous research [25]. During experiments, the authors observed that linear classification is much more accurate than nonlinear.…”
Section: Resultsmentioning
confidence: 73%
“…The time, space, and place in the consumption process is visible now in the purchasing behavior with the social distancing, the healthy distance, and the commercial restriction caused by the Covid-19 health contingency. Despite being, above all, health -and also a humanitarian-crisis, the Covid-19 pandemic presents severe economic consequences throughout the world ( Cox, 2020 ), as an increase in unemployment rates ( Hall, 2020 ; Rushe and Aratani, 2020 ) collapsed health systems ( Washingtonpost, 2020 ), education models overwhelmed by technology ( worldbank, 2020 ), supply chains disrupted by border closings ( Buchholz, 2020 ; Salcedo et al., 2020 ), international and domestic tourism suspended due to a lack of sanitary protocols ( OECD, 2020 ), social coexistence curtailed by significantly increased infections ( Dubey et al., 2020 ) and a decreasing demand by consumers for the closure of companies ( Szymkowski et al., 2020 ), mainly in small and medium-sized companies (SMEs). These factors are also part of the purchasing behavior that is changing ( Dooley et al., 2010 ; Foxall, 1979 ; Lamming, 2000 ; Habel et al., 2020 ).…”
Section: Conceptualization Of Purchase Behavior In Times Of Pandemicmentioning
confidence: 99%
“…At the same time, modern technologies have gathered more interest. Artificial intelligence (AI) and ML can be used in numerous applications such as cybersecurity [ 2 ], pedestrian detection [ 3 ], telemedicine [ 4 ], biometrics [ 5 ] or sports analytics [ 6 ]. Thus, the implementation of AI and ML in COVID-19 and other lung diseases seems to be the desired natural progression.…”
Section: Introductionmentioning
confidence: 99%